2019
DOI: 10.4103/ijn.ijn_251_18
|View full text |Cite
|
Sign up to set email alerts
|

Hand grip strength in patients on maintenance hemodialysis: An observational cohort study from India

Abstract: Introduction:Malnutrition is a common manifestation in patients with dialysis and is a major cause of mortality in these patients. Various biochemical parameters are used to detect and monitor malnutrition in these patients. Confounding variables present in hemodialysis have an effect on the sensitivity and specificity of these tests.Methods:We studied hand grip strength (HGS) as a monitoring tool for protein malnutrition in these patients.Results:In a prospective observational study over 18 months, 83 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…In our study, 21 patients (10.8%) had pedal edema despite thrice per week MHD. In contrast to our study, an Indian study showed pedal edema in 50% of the study population [ 14 ]. Ideally, the anthropometric measurements should be done at the correct dry weight of the patient when he/she is free of excess fluid to give an accurate picture of the nutritional status.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, 21 patients (10.8%) had pedal edema despite thrice per week MHD. In contrast to our study, an Indian study showed pedal edema in 50% of the study population [ 14 ]. Ideally, the anthropometric measurements should be done at the correct dry weight of the patient when he/she is free of excess fluid to give an accurate picture of the nutritional status.…”
Section: Discussioncontrasting
confidence: 99%
“…The functional status of general muscle strength is correlated consistently with the extent of HGS. In an Indian study, HGS in most males was weak compared to the general population of the same age group [ 14 ]. In our study, males have weaker HGS as compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the handgrip results indicate early nutrition status deterioration, which facilitates prompt and early intervention. [19] Our findings showed that the malnourished HD patients recorded lower handgrip values ( P = .011) compared to the well-nourished HD patients (18.3 ± 12 and 21.5 ± 11.9, respectively). This observation could be attributed to potential muscle weakness in response to malnutrition.…”
Section: Discussionmentioning
confidence: 66%
“…This observation could be attributed to potential muscle weakness in response to malnutrition. [19] It is well known that muscle mass, as measured by fat-free mass, is higher in well-nourished HD patients than in malnourished patients. [20] This is in agreement with our findings, where the impact of malnutrition yielded comparable results by reducing both muscle mass and handgrip values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation